Distributed consensus via self‐triggered output feedback. Issue 10 (1st June 2016) - Zhao, Jianfeng; Xiang, Linying; Chen, Fei; Lan, Weiyao
Abstract : The consensus problem based on output feedback is addressed in this study for general linear multi‐agent systems under a distributed self‐triggered control framework. Two kinds of distributed output feedback control algorithms, one for local static output feedback and the other for observer‐type dynamic feedback, are designed to solve the consensus problem by employing the distributed self‐triggered control strategy, where each agent calculates its next update instant based on the local information at the last update instant. It is shown that consensus can be reached asymptotically under the two proposed control algorithms. Finally, two simulation examples are given to verify the theoretical results.